Does Multiple Intelligence Improve Performance? Evidence from a Case at Kampala International University - Kiggundu, Z. F. (African Journals Online (AJOL), 2011)
This study reports the findings of a study that investigated the relationship between multiple intelligence (MI) and academic performance in higher education. It addresses one question: does MI improve academic performance? Taking the case of the finalist cohort of the university’s Faculty of Education of the academic year 2009/2010, data were collected on students’ MI and performance. Subsequently, the data were subjected to linear regression analysis. The findings were that the relationship between MI and students’ academic performance was not statistically significant. Accordingly, the study lends credence to the traditional conceptualization of the concept of intelligence. Therefore, the paper recommends that higher education institutions continue paying attention to the factors that have traditionally been known to influence academic performance.